Mad skills : drifting with Rhys Millen - Coal, Carolyn; Millen, Rhys 1972-; Foust, Tanner, 1973-; Hubinette, Samuel; Millen, Rod, 1951-; NoCo Media Group; Leomark Studios ([Los Angeles, California] : NoCo Media Group, 2008)
Champion drifter Rhys Millen revisits the exhilaration and intensity of the 2005 Formula D Season in the action packed documentary Mad Skills. Coming off a potentially disastrous crash in Chicago, Millen and his crew have less than a week to get his GTO ready for the finals in Irwindale. Complicating matters, the RX8 Rhys built for his father, the legendary rally driver Rod Millen, may not be able to compete in the final race. Battling mechanical difficulties, crew troubles and formidable competitors including his good friends Samuel Hubinette and Tanner Foust, Rhys must remain sharply focused to ensure his victory and win the championship. Filled with explosive door-on-door action, tire smoke and out control spins Mad Skills offers a never-before-seen look into the art of driving sideways. Once you've seen it, you'll never look at motor sports in the same way. --
Originally released as a motion picture in 2009.
Rhys Millen, Tanner Foust, Samuel Hubinette, Rod Millen.
Editor, Ryan Halferty, Adam Levine ; music, Marika Tjelios.
In English; closed captioning available.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed January 15, 2021)
Keywords: Millen, Rhys -- 1972-; Drifting (Motorsport); Automobile racing -- Competitions; Automobile racing drivers; Sports films; Nonfiction films; Documentary films; Internet videos; Streaming video